Access to Controlled Medications: Barriers, Measuring Adequacy of Consumption, and Current Developments. Issue 1 (31st August 2020) - Scholten, Willem
Access to controlled medications is problematic in many countries, in spite of the objectives of the international substance control conventions. The review describes barriers for accessing medications and how to assess the adequacy of opioid analgesic consumption globally. As current trends in consumption, it discusses the lack of progress of improving access and the threat of the false narrative that people who suffer moderate to severe pain are the cause of an epidemic of opioid intoxications. Finally, it questions the feasibility of an approach which requires large numbers of anaesthesiologist for treating chronic pain, and wonders what the effect of the COVID-19 pandemic on accessibility to controlled medications will be.